2010
DOI: 10.1017/s0029665110000157
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and use of n-3 fatty acids in artificial nutrition

Abstract: Lipids traditionally used in artificial nutrition are based on n-6 fatty acid-rich vegetable oils like soyabean oil. This may not be optimal because it may present an excessive supply of linoleic acid. One alternative to the use of soyabean oil is its partial replacement by fish oil, which contains n-3 fatty acids. These fatty acids influence inflammatory and immune responses and so may be useful in particular situations where those responses are not optimal. Fish oil-containing lipid emulsions have been used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 95 publications
(179 reference statements)
1
63
0
1
Order By: Relevance
“…The absorption of fat is compromised and, in such conditions, it is of great importance to ensure that EFAs are delivered to the body (8). The above conditions can be caused by different diseases and related risk factors, such as chronic pancreatitis, Crohn's disease, cystic fibrosis, Shwachman-Diamond syndrome, or history of previous surgery (e.g., ileal resection, bariatric surgery) on the gastrointestinal (GI) tract (9)(10)(11). Because of the modified anatomy in some bariatric surgery procedures (e.g., biliopancreatic diversion) or extensive resection of the small bowel, both digestion and absorption of nutrients is altered and can lead to a delayed mixing of fat with pancreatic enzymes and bile salts, thereby lowering levels of some nutrients, such as fat-soluble vitamins (12)(13)(14).…”
Section: Participants and Anthropometric Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption of fat is compromised and, in such conditions, it is of great importance to ensure that EFAs are delivered to the body (8). The above conditions can be caused by different diseases and related risk factors, such as chronic pancreatitis, Crohn's disease, cystic fibrosis, Shwachman-Diamond syndrome, or history of previous surgery (e.g., ileal resection, bariatric surgery) on the gastrointestinal (GI) tract (9)(10)(11). Because of the modified anatomy in some bariatric surgery procedures (e.g., biliopancreatic diversion) or extensive resection of the small bowel, both digestion and absorption of nutrients is altered and can lead to a delayed mixing of fat with pancreatic enzymes and bile salts, thereby lowering levels of some nutrients, such as fat-soluble vitamins (12)(13)(14).…”
Section: Participants and Anthropometric Measurementsmentioning
confidence: 99%
“…In subjects who have undergone major GI surgery, LC-PUFA supplementation has been shown to reduce concentrations of inflammatory biomarkers and to shorten hospital length of stay (11,12). According to previous studies, EFAs delivered as MAG have been reported to be better absorbed than EFAs delivered as TAG (18)(19)(20)(21).…”
Section: Participants and Anthropometric Measurementsmentioning
confidence: 99%
“…Given that 9,10-DiHOME production is catalyzed by the sEH, it is not surprising that sEH inhibitors were able to provide protection in such a situation. However, a simpler approach was simply to reduce the concentration of linoleic acid in the parenteral nutrition given to patients, an intervention that resulted in marked benefits in gas exchange, ventilation requirement, and mortality (Calder, 2010).…”
Section: G Metabolism and Diabetesmentioning
confidence: 99%
“…There are 2 prescription formulations of n-3 LCPUFAs available in the United States: the v-3 acid ethyl esters (LOVAZA) and the icosapent ethyl (VASCEPA). Some formulas designed for enteral or parenteral use contain n-3 LCPUFAs (1,8).…”
Section: Clinical Usesmentioning
confidence: 99%